2D фотонно-кристалiчний резонатор острiвкового типу - Glushko, E. Ya. (Publishing house "Academperiodika", 2018)
A binary island-kind photonic crystal resonator is investigated analytically and numerically in the framework of the standing wave expansion method. The photonic bandgap structure for a finite SiO2/SiO2 resonator with rectangular elementary cell of micron sizes is first calculated. The classification concept of resonator’s modes is proposed. The field distribution inside the resonator is calculated, and some ways to use the island resonators in optical devices are discussed.